Integrating Indigenous Cultural-Based Learning to Enhance Spatial Reasoning among Canadian Secondary School - Rodríguez, Ana; Thompson, Liam; Dubois, Sophie (SCIENTIA: Journal of Multi Disciplinary Science, 2025)
This study investigates the effectiveness of an Indigenous cultural-based learning (ICBL) approach in enhancing spatial reasoning among Canadian secondary school students. Recognizing that spatial thinking is a foundational skill for mathematics, science, and geography education, the research explores how integrating Indigenous cultural knowledge—particularly First Nations’ geometric patterns, Inuit mapping traditions, and Métis beadwork symmetry—can support students’ conceptual understanding of spatial relationships. A quasi-experimental design was implemented with 238 Grade 9 students from two public secondary schools in British Columbia. The experimental group received twelve weeks of geometry instruction incorporating Indigenous cultural contexts, while the control group followed a conventional curriculum. Spatial reasoning was measured using the Purdue Spatial Visualization Test: Rotation (PSVT:R) and a spatial problem-solving assessment developed for this study. ANCOVA results revealed a significant improvement in spatial reasoning scores in the experimental group (F(1,235)=18.72, p<0.001, η²=0.074), indicating that culturally embedded pedagogies effectively enhanced students’ spatial understanding. Qualitative feedback from students also highlighted greater engagement, cultural appreciation, and cognitive flexibility. The findings contribute to growing evidence on the pedagogical value of cultural responsiveness in STEM education and underscore the importance of integrating Indigenous knowledge as a legitimate epistemological framework in Canadian classrooms.